(565) On The Matrix Method For Solving Linear-differential Eques حول طريقة المصفوفة لحل المعادلات التفاضلية الخطية - Hassan, Ahmad; Fouad, Afaf; El Gindi, Salah (معهد التخطيط القومى, 2024)
Several methods have been proposed for solving ordinary differential equations which take advantage of the special properties of Chebyshev polynomials. For the sake of completeness, we are going to mention here some of the methods which use these polynomials for solving differential equations. For the properties of Chebyshev polynomials we refer to (Memo. no. ).